Analisis Kontrastif Adverbia Yang Menyatakan Kepastian Dalam Bahasa Jepang Dan Bahasa Indonesia - Krisnanda, Shindu; Wikarya, Rahmi Oktayory (Universitas Negeri Padang, 2024)
Adverbs that express certainty in Japanese are often difficult for Indonesian learners due to the lack of equivalent references. The adverbs are kitto, kanarazu, zehi, and zettaini. This contrastive analysis research will discuss the equivalence of Japanese certainty adverbs with Indonesian adverbs that use the words certain, sure, and undoubtedly with semantic studies. In addition, it will be investigated what matching phenomena occur between the meanings of the two languages. This type of research is expected to help Japanese learners to better understand the meaning of adverbs that express certainty. The results of this study show that kitto, kanarazu, zehi, and zettaini can be paired with Indonesian adverbs pasti, tentu, and undoubtedly. Kitto can be paired with certain, kanarazu can be paired with certain, zehi, can be paired with certain, and zettai ni can be paired with certain.